A Hydrothermal-Assisted Ball Milling Approach for Scalable Production of High-Quality Functionalized MoS2 Nanosheets for Polymer Nanocomposites - Mojtaba Ahmadi (Nanomaterials, 2019)
The most known analogue of graphene, molybdenum disulfide (MoS2) nanosheet, has recently captured great interest because it can present properties beyond graphene in several high technological applications. Nonetheless, the lack of a feasible, sustainable, and scalable approach, in which synthesizing and functionalization of 2H-MoS2 nanosheets occur simultaneously, is still a challenge. Herein, a hydrothermal treatment has been utilised to reduce the effect of breaking mechanisms on the lateral size of produced nanosheets during the ball milling process. It was demonstrated that the hydrothermal pre-treatment led to the initial intercalation of an organic molecule such as 4,4′-diaminodiphenyl sulfone (DDS) within the stacked MoS2 sheets. Such a phenomenon can promote the horizontal shear forces and cause sliding and peeling mechanisms to be the dominated ones during low energy ball milling. Such combined methods can result in the production of 2H functionalized MoS2 nanosheets. The resultant few layers showed an average lateral dimension of more than 640 nm with the thickness as low as ~6 nm and a surface area as high as ~121.8 m2/g. These features of the synthesised MoS2 nanosheets, alongside their functional groups, can result in fully harnessing the reinforcing potential of MoS2 nanosheets for improvement of mechanical properties in different types of polymeric matrices.